STRUCTURAL AND CELLULAR RECONSTRUCTION OF LYMPH NODES IN EXOTOXICOSIS - Akhmad Nurgulim; Dyussembayeva Asya; Abilova Altyn (Scientific Results, 2026)
Modern conditions are characterized by increasing adverse environmental impacts on the human and animal body. The place and role of lymph nodes as biological filters for the lymph flowing through them are now clearly defined. Lymph nodes have already established a strong role in the immune system. Detoxification processes in regional lymph nodes are studied by influencing the lymph entering the lymph nodes with biophysical, biochemical, and immune factors. Natural lymph node detoxification determines the quality and effectiveness of tissue and organ detoxification